2021
DOI: 10.1155/2021/4009308
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Pathway Ameliorates Bladder Dysfunction in Cyclophosphamide‐Induced Cystitis via Suppression of Oxidative Stress

Abstract: Objective. To investigate the protective effect and molecular mechanism of nuclear factor E2-related factor 2 (Nrf2) pathway in interstitial cystitis (IC). Methods. We established a mouse model of IC by cyclophosphamide (CYP) in wild-type mice and Nrf2 gene knockout mice. We examined the histological and functional alterations, the changes of oxidative stress markers, and the expression of the antioxidant genes downstream of Nrf2 pathway. Results. After CYP administration, the mice showed urinary frequency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Nrf2 not only mediates an effect in the cardiac tissue only, but also in other organs. For instance, the Nrf2 pathway ameliorated bladder dysfunction in cyclophosphamide-induced cystitis through oxidative stress suppression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 not only mediates an effect in the cardiac tissue only, but also in other organs. For instance, the Nrf2 pathway ameliorated bladder dysfunction in cyclophosphamide-induced cystitis through oxidative stress suppression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the production of ROS is central to the progression of many inflammatory diseases [27] and has already been identified as an important underlying feature in IC/BPS pathobiology [28,84,85], we herein evaluated the effects of TNFα on the production of ROS and how this is affected by concomitant treatment with CBD. The production and maintenance of controlled levels of intracellular ROS are critical for cells to perform a number of physiological functions, including maintenance of redox homeostasis, cell cycle signaling, and hormone production [86].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 was recently identified as one of the contributors to IC/BPS by Ni et al [85]. They showed that nrf2 knockout mice with an experimentally induced cystitis developed more severe symptoms of IC/BPS and bladder injury with structural destruction of the urothelium compared to wild type mice [85].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NrF-2 diminishes bladder dysfunction through suppressing oxidative stress 31 . Ni, et al 32 showed that NrF-2 knockout mice presented more severe symptoms of cystitis after cyclophosphamide administration, followed by a decrease in SOD-1 activity and increase in mRNA expression of HO-1 and NQO-1. mRNA expression of HO-1 and NQO-1 after IFO-induced cystitis was also described by Kim, et al 33 .…”
Section: Discussionmentioning
confidence: 99%